Mineral trioxide aggregate (MTA) in dentistry: A review of literature - Chirag Macwan; Anshula Deshpande (Wolters Kluwer Medknow Publications, 2014)
Mineral trioxide aggregate (MTA) is a unique material with several exciting clinical applications. MTA has potential and one of the most versatile materials of this century in the field of dentistry. During endodontic treatment of primary and permanent tooth MTA can be used in many ways. MTA materials have been shown to have a biocompatible nature and have excellent potential in endodontic use. MTA materials provide better microleakage protection than traditional endodontic repair materials using dye, fluid filtration, and bacterial penetration leakage models. In both animal and human studies, MTA materials have been shown to have excellent potential as pulp-capping and pulpotomy medicaments. MTA material can be used as apical and furcation restorative materials as well as medicaments for apexogenesis and apexification treatments. In present article, we review the current dental literature on MTA, discussing composition, physical, chemical and biological properties and clinical characteristics of MTA.